Penurunan Kadar Gula Darah Pasien Diabetes Mellitus setelah Mengkonsumsi Air Rebusan Bunga Telang: Studi Kasus - Novita, Rosdiana Della; Milwati, Susi; Setyarini, Anggun (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Efforts to reduce and control blood sugar levels in Diabetes Mellitus patients previously used pharmacological therapy, but diabetes mellitus sufferers felt that pharmacological therapy alone was less effective in lowering blood sugar levels. The butterfly pea flower, which is easy to find in people's yards, is then used by diabetes mellitus sufferers as an alternative therapy to lower blood sugar levels while maintaining pharmacological therapy. The chemical compounds contained in butterfly pea flowers such as flavonoids and phenolics can be used as antidiabetics. This study aims to identify changes in blood sugar levels of Diabetes Mellitus patients after consuming boiled water from Telang Flowers (Clitoria Ternatea). This research uses a case study approach. There were 2 research subjects according to the inclusion criteria, namely subjects diagnosed with type 2 DM, subjects taking DM medication prescribed by a doctor, and having consumed boiled water from butterfly pea flowers for at least 1 month. Data collection in this research used interviews, questionnaires and observation. Blood sugar monitoring was carried out for 1 month. Subject 1 experienced a total decrease in fasting blood sugar of 81 mg/dL. Subject 2 experienced a total decrease in fasting blood sugar of 94 mg/dL. Subject 2 who consumed butterfly pea flowers every day experienced a greater decrease in blood sugar levels than subject 1 who consumed butterfly pea flowers 2-3 times/week. Based on the experience of the two subjects in consuming telang flowers, it can be concluded that telang flowers can be used as an alternative therapy to lower blood sugar. Consuming butterfly pea flowers every day lowers blood sugar more quickly, has no adverse side effects and is safe to consume.